Evaluation of Covid-19 protection knowledge and practice of dentists in Isfahan in clinical environment - Parichehr Behfarnia; Omid Fakheran; Zahra Zargar (Tehran University of Medical Sciences, 2022)
Background and Aims: The 2019 coronavirus pandemic has resulted in a lot of pressure on health systems around the world. The risk of transmission of infection in dentistry is significantly high. The aim of this study was to evaluate Covid-19 protection knowledge and practice of dentists in Isfahan in clinical environment. Materials and Methods: In this study which was performed in April 2021 by available sampling method, an online questionnaire was used as a data collection tool. Questions included demographic characteristics, knowledge of proper protective protocols, protection protocols taken against Covid-19, and the prevalence of Covid-19 infection. Descriptive and analytical analyzes were performed using SPSS26 software including frequency distribution tables, graphs, independent t-test, and Pearson and Spearman correlation coefficients. Results: 310 questionnaires were collected with complete answers. 87.4% of dentists had moderate and high knowledge of proper protective protocols against Covid-19. The mean knowledge score had no significant relationship with the demographic characteristics of age (P=0.59), gender (P=0.31 and r=0.05), work experience (P=0.16 and r=0.07) and degree (0.33=P). In the pandemic period, 87% of dentists treated dental emergencies and 40% delayed the dental treatment for patients with high risk of Covid-19. Dentists used personal protective equipment correctly. Among all the included dentists, 75% used high protection masks, 75% used face shields, 67% used hats, and 60% used sterile gowns in all of their treatment activities. The clinical environment was equipped well to prevent spreading of Covid-19. The results showed that 55.8% of the participants had one or more similar signs/symptoms of Covid-19 and 9% had a positive SARS-CoV-2 test during the last months. Conclusion: The majorities of dentists had enough knowledge of proper protective protocols against Covid-19 and efficiently used all protections while performing dental procedures.